Melting of cryocrystasls at high pressures. Computer simulation - Yakub, E. (Хабаршы. Физика сериясы, 2015)
Two types of molecular dynamics simulations: single-phase and two-phase carried out and applied to determine the melting temperatures of highly compressed diatomic cryocrystals: nitrogen and hydrogen, as functions of pressure. Solid hydrogen was modeled by two approximations (1) non-empirical atom-atom potential (AAP) approximation [1], and diatom-diatom (DDP) approximation. Within AAP-model potential energy of hydrogen molecules is represented as a function of interatomic distances between all atoms as a sum of intramolecular (bonding) and intermolecular (non-bonding) parts. Both types of potentials are expressed via known potential energies of two isolated hydrogen atoms in the singlet and triplet states.